2013
DOI: 10.1371/journal.pone.0063967
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced M2 to M1 Macrophage Transformation for IL-12p70 Production Is Blocked by Candida albicans Mediated Up-Regulation of EBI3 Expression

Abstract: Macrophages are heterogeneous cell populations that are present in all tissues. Macrophages can be divided into classically activated inflammatory macrophages (M1) and alternatively activated anti-inflammatory macrophages (M2). It has been generally accepted that M1 macrophages are polarised in an inflammatory environment to produce pro-inflammatory cytokines, whilst M2 macrophages are involved in anti-inflammation and aid tissue repair in wound healing. Bacterial endotoxin (lipopolysaccharide; LPS) is a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 32 publications
11
76
0
Order By: Relevance
“…LPS also suppressed Ebi3 mRNA expression in a mouse macrophage line RAW264.7 cells (Supporting Information Fig. 1) consistent with the previous report that Ebi3 expression is decreased in LPS-induced M2 to M1 macrophage transformation [39]. These results suggest that the complex effects of LPS on p19 and Ebi3 expression in DCs, macrophages and B cells require additional studies.…”
Section: Discussionsupporting
confidence: 90%
“…LPS also suppressed Ebi3 mRNA expression in a mouse macrophage line RAW264.7 cells (Supporting Information Fig. 1) consistent with the previous report that Ebi3 expression is decreased in LPS-induced M2 to M1 macrophage transformation [39]. These results suggest that the complex effects of LPS on p19 and Ebi3 expression in DCs, macrophages and B cells require additional studies.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies on M2 function have failed to take into account the importance of a priming signal, normally delivered by a toll-like receptor (TLR) ligand, in inflammasome activation. Priming macrophages with LPS for longer than was done in this study can also shift macrophage polarisation 53. In our study, primed M1′ and M2′ macrophages still expressed typical M1 and M2 markers.…”
Section: Discussionsupporting
confidence: 46%
“…Lipopolysaccharide (LPS) has been reported to induce an M1 phenotype from an M2 phenotype. 77 Furthermore, tumor-mediated M2-like macrophages can be reprogrammed to M1-like cells by activation of CD40 using IFN-g. 78 Furthermore, reports have indicated that when fully polarized M2 macrophages present antigen to Th1 cells in a tumor milieu, this interaction results in repolarization of M2 to M1 macrophages. 79 …”
Section: Can Macrophages Switch Polarization State?mentioning
confidence: 99%